Academic Material Processes Usage in Research Articles (Revista de Estudos da Linguagem, 2024)
This research aimed to analyze the most frequent academic material clauses in a corpus of scientific articles, based on Systemic-Functional Linguistics (LSF), mainly Halliday and Matthiessen (2014). For that, we used Corpus Acadêmico do Português Brasileiro (CAPB), a corpus representative of the genre in question, with approximately 12.3 million words. Our goal was to observe possible differences and similarities in the use of material processes in different disciplines. For the analysis, samples of the most frequent material processes in the corpus were selected. According to research carried out by Miranda (2021), among the ten most frequent academic verbs, six instantiated material sentences, namely: apresentar, utilizar, realizar, encontrar, analisar and determinar. In this research, these verbs were studied in their realization as material clauses, taking into account the area of knowledge in which they occurred, as well as their uses and implications within the text. It was observed that material processes occurred similarly across different areas of knowledge in order to describe and report experiments, analyses, recommendations and authors’ contributions to the field. However, through the contrastive study between the areas of knowledge, we perceived differences regarding the way each discipline chose to use the material processes and, consequentially, in the textual implications caused by those choices. Finally, the results contribute to a deeper understanding of academic writing, advancing theoretical studies in Portuguese based on LSF.